Investigation of road marking identification algorithms - Zvyagintsev D. A. (Scientific research and developments of students, 2016)
the article shows the data on experiments revealing qualitative characteristics of road marking identification algorithms as well as their comparison.
Keywords: системы помощи водителю; система распознавания дорожной разметки; ADAS; ADAS; driver helping systems; road marking recognition system